Prospects and Dilemmas of Endovascular Treatment for Vertebrobasilar Dolichoectasia - Wang, Yiheng; Yu, Jinlu (Frontiers in Neurology, 2022)
Vertebrobasilar dolichoectasia (VBD) is characterized by significant expansion, elongation, and tortuosity of the basilar artery and vertebral artery. Certain highly selected VBDs can require intervention. Recent advances in endovascular treatment (EVT) have renewed hope for patients with VBD. However, which VBDs can benefit from EVT still needs to be determined. Currently, little is known regarding this matter. Therefore, we performed a review of the literature from a PubMed search and cataloged our experience regarding the classification and natural history of VBD and the prospects, prognosis and complications of EVT. The findings can be summarized as follows: for asymptomatic VBD, “wait and see” or medical management may be a reasonable strategy. EVT may only be effective in certain patients. For saccular aneurysms, especially ruptured aneurysms, EVT is reasonable. For fusiform aneurysms, EVT can carry high complication rates and should be recommended with caution. For stenting reconstruction in VBD, the effect is uncertain. For the future of EVT of VBD, randomized controlled trials and the development of neurointervention products are worth pursuing, but EVT in VBD still has a long way to go.